About the features of the water-bodies monitoring at the surface water-intake facilities of the oil fields of the Far North - S. D. Ganova; M. N. Tsymbal (Известия высших учебных заведений: Геология и разведка)
The practice of the exploitation of hydrocarbon deposits of the Far North shows that despite the complexity and interdependence of natural and man-made conditions, the design of structures uses a certain set of solutions related to the characteristics of the area. The main fact is that all linear objects are designed in one corridor, at the same time, pipelines (oil pipelines, water conduits) are designed for ground laying on piles, areal objects (infrastructural sites) on the embankment with the preservation of the soil and vegetation layer at the base of the embankment. In addition, speaking about the field development or the transport of the product, unreasonably little attention is paid to the objects that ensure the operation of the main objects in normal mode. Such objects, in particular, are the water conduits and water-intake structures that provide an uninterrupted supply of water of the desired quality and quantity on the area of support base of the field of deposits. Despite the rather strict environmental legislation, it is impossible to take into account all the factors of negative impact on the environment, it is even more difficult to monitor the effect of a complex of these factors, and especially the interaction of all objects, processes and phenomena within the current natural and technical system.